Adaptive Reuse of Industrial Heritage Sites for Sustainable Urban Development - Wei, Qisi; Utaberta, Nangkula; Zainordin, Nadzirah (Journal of Ecohumanism, 2025)
The research aims at future urban transformation and development by rediscovering the industrial heritage in the 798 Art Zone, Beijing and the M50 Creative Plaza, Shanghai. In the assessment of the criteria, benefits and success factors of adaptive reuse projects, the research employs the use of both quantitative (questionnaires) and qualitative (case studies) methods. The following points have been identified such as government incentives, local engagement, and retaining the appearance of industrial structures. Drawing from industrial heritage architecture, the study reveals the economic, environmental, and social benefits of retrofitting industrial structures, increased economy revitalisation and cultural identity, and the mitigation of new construction. However, the research found some drawbacks of the study such as the absence of unified conceptual frameworks that cover all four dimensions of sustainability and the uncertainty associated with technical and regulatory factors. This work, therefore, points out that, while adaptive reuse projects are critical to the augmentation of urban regeneration, there exist hurdles that require deliberate effort to be surmounted. Based on these findings, suggestions are given for improvement to policies for government, political parties, urban designers and developers to improve the comprehensiveness of pro-historical building reuse policies. This work finally suggests a framework for further research on any adaptive reuse projects to inform future sustainable design efforts that take into consideration the exploration of resources of the culture and ecosystems.